East Asia Update, April 2005 : East Asia's Dollar Influx - Signal for Change - World Bank (World Bank, Washington, DC, 2020)
Economic growth in Emerging East Asia reached a cyclical peak of 7.2 percent in 2004 from which it is expected to slow only moderately to about 6 percent in 2005 and 2006. The tragic tsunami disaster, while it had a horrendous impact in terms of loss of life, is expected to have only a limited impact on overall economic growth in the two most seriously affected East Asian economies, Indonesia and Thailand. Among the developing economies in the region growth is expected to ease from over 8 percent - the highest since before the financial crisis - to around 7 percent in the coming period.